Stakeholder Identification and Collaboration Indicators in The Construction of Pedestrian Facilities in Jakarta - Adikara, Kharisma; Machfudiyanto, Rossy Armyn (Journal La Multiapp, 2024)
One of the programs the Jakarta Capital City Government runs is to lower the traffic in the city by offering spacious and comfortable pedestrian areas. The entire street idea, which divides road space to accommodate different user kinds and abilities, including those with disabilities, is used in its implementation. However, Stakeholder participation has certain drawbacks, including poor institutional coordination and subpar program execution integration with pertinent regional apparatus. This issue is believed to arise when multiple stakeholders' interests are involved, leading to disparities in sectoral perspectives and egos. These issues also make it more challenging to carry out the program's provision of pedestrian amenities. This research identifies internal and external stakeholders who influence the construction of pedestrian facilities in Jakarta and identifies indicators that affect their collaboration.